2016
DOI: 10.1111/jpi.12310
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents abnormal mitochondrial dynamics resulting from the neurotoxicity of cadmium by blocking calcium‐dependent translocation of Drp1 to the mitochondria

Abstract: Cadmium (Cd) is a persistent environmental toxin and occupational pollutant that is considered to be a potential risk factor in the development of neurodegenerative diseases. Abnormal mitochondrial dynamics are increasingly implicated in mitochondrial damage in various neurological pathologies. The aim of this study was to investigate whether the disturbance of mitochondrial dynamics contributed to Cd-induced neurotoxicity and whether melatonin has any neuroprotective properties. After cortical neurons were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 50 publications
4
78
0
Order By: Relevance
“…However, the molecular signals that lie downstream of the Hippo-Yap pathway in cancer remain largely uncharacterized. Our present study found that mitochondrial fission was a novel sequential signal of the Hippo-Yap pathway in RC tumorigenesis and metastasis [48]. Yap functions through its direct interaction with JNK to suppress Drp1-mediated mitochondrial fission, sustaining RC growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular signals that lie downstream of the Hippo-Yap pathway in cancer remain largely uncharacterized. Our present study found that mitochondrial fission was a novel sequential signal of the Hippo-Yap pathway in RC tumorigenesis and metastasis [48]. Yap functions through its direct interaction with JNK to suppress Drp1-mediated mitochondrial fission, sustaining RC growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, mitochondria undergo continual fusion and fission to maintain the cellular energetic demands. A shift to excessive fission causes an increase in non-functional mitochondria debris [48], and this mitochondrial debris contains pro-apoptotic factors, such as cyt-c, Smac and HtrA2/Omi, which disrupt the balance between cellular survival and apoptosis [53]. In this study, we found that loss of Yap triggered the leakage of HtrA2/Omi from mitochondria into the cytoplasm via activation of mitochondrial fission, leading to a marked drop in anti-apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were subsequently scraped, and the homogenates were spun at 800 x g for 5 minutes at 4°C. The supernatants were centrifuged at 10, 000 x g for 20 min at 4°C to acquire the pellets, which were spun again [6,24]. The final pellets were suspended in lysis buffer containing 1% Triton X-100 and were noted as mitochondrial-rich lysate fractions [34].…”
Section: Isolation Of Mitochondrial-enriched Fractionmentioning
confidence: 99%
“…These data indicate that mitochondria homeostasis could be considered a therapeutic target for the treatment of endometriosis. Notably, recent studies show that mitochondrial dynamics, especially Drp1-related mitochondrial fission, happen at the early stage of cellular apoptosis, such as in liver cancer, cardiomyocytes and neurocytes [6,7]. Excessive mitochondrial fission initiates caspase 9-related mitochondrial apoptosis, leading to cell death [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the samples were blocked with 10% goat serum albumin (Invitrogen, USA) for 1 h at room temperature and subsequently incubated with primary antibodies overnight at 4°C [33]. After three rinses in PBS, secondary antibodies were added to the samples for 1 h at room temperature [34].…”
Section: Methodsmentioning
confidence: 99%